New polyfunctional dendritic linear hybrids from terminal amine polyether oligomers (Jeffamine®): Synthesis and characterization - Froimowicz, Pablo (2005)
New dendritic polyether oligomers were synthesized from three different Jeffamines® and characterized. This class of polyfunctional oligomers, bearing on their surface methylester, carboxylic acid, nitrile or amine groups, could be interesting modifying agents to change the properties of materials. The optimization of the iterative synthetic methods, through Michael addition, hydrolysis or hydrogenation, gave first and second generation dendritic structures in good yields.